2000
DOI: 10.1080/00498250010002252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clofibrate and indocyanine green on the hepatobiliary disposition of acetaminophen and its metabolites in male CD-1 mice

Abstract: 1. The effects of clofibrate (CFB) and indocyanine green (ICG) on the biliary excretion of acetaminophen (APAP) and its metabolites were investigated. 2. Male CD-1 mice were pretreated with 500 mg CFB/kg, i.p. for 10 days. Controls received corn oil vehicle only. After overnight fasting, common bile duct-cannulated mice were challenged with a non-toxic dose of APAP (1 mmol/kg, i.v.). 3. CFB pretreatment did not affect bile flow rate, nor did it affect the cumulative biliary excretion of APAP and its conjugated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…Recently, Brouwer and coworkers (Xiong et al, 2000) reported that the biliary excretion of APAP-GLU and, to a lesser extent, APAP-SUL, was impaired in isolated perfused livers from TR Ϫ rats, which indicates the involvement of Mrp2 in the hepatobiliary transport of these two metabolites. Their results are in agreement with our observations that the biliary concentration of APAP-GLU, but not that of APAP-SUL, is significantly decreased by coadministration of the organic anion ICG (Chen et al, 2000). Their studies, however, did not examine the biliary disposition of APAP-GSH and its hydrolytic derivatives, which are reflective of APAP oxidation by cytochrome P450.…”
supporting
confidence: 82%
See 4 more Smart Citations
“…Recently, Brouwer and coworkers (Xiong et al, 2000) reported that the biliary excretion of APAP-GLU and, to a lesser extent, APAP-SUL, was impaired in isolated perfused livers from TR Ϫ rats, which indicates the involvement of Mrp2 in the hepatobiliary transport of these two metabolites. Their results are in agreement with our observations that the biliary concentration of APAP-GLU, but not that of APAP-SUL, is significantly decreased by coadministration of the organic anion ICG (Chen et al, 2000). Their studies, however, did not examine the biliary disposition of APAP-GSH and its hydrolytic derivatives, which are reflective of APAP oxidation by cytochrome P450.…”
supporting
confidence: 82%
“…With the recent identification and characterization of several apical and basolateral transporters (Muller and Jansen, 1997), it is now clear that the hepatic levels of some transport systems can be modulated by prototypical microsomal inducers such as pregnenolone 16␣-carbonitrile (Salphati and Benet, 1998), dexamethasone (Courtois et al, 1999), and phenobarbital (Ogawa et al, 2000). Therefore, these types of APAP disposition studies should be interpreted with respect to both xenobiotic inducibility of hepatic transporters and molecular mechanisms for the hepatic excretion of APAP and its metabolites.We recently showed that the biliary concentration of APAP-GSH, APAP-NAC, and APAP-GLU, but not that of APAP itself, APAP-SUL or APAP-CG/CYS, was significantly decreased by coadministration of the nonmetabolizable organic anion indocyanine green (ICG) in male CD-1 mice (Chen et al, 2000). These findings suggest that several APAP conjugates share hepatobiliary transport systems with ICG.…”
mentioning
confidence: 84%
See 3 more Smart Citations